Censorship detected in IR (Iran) - Voidly (2025)
CRITICAL severity censorship detected in Iran. Confidence: 75%. Data sourced from CensoredPlanet.
Censorship Incident ID: IR-2025-0008
Keywords: censorship; IR; censorship; critical